PERBEDAAN pH SALIVA MENGUNYAH PERMEN KARET XYLITOL DAN SUKROSA DI SDN 2 GUNTUNG PAIKAT BANJARBARU - hafizatunnadia, hafizatunnadia; salamah, siti; fansurna, anderi (Poltekkes Kemenkes Banjarmasin, 2022)
n Indonesia, the sweetest gum is consumed by children. One of them is sucrosegum, which has a sweet, varied texture and shape. This is a factor that causes an increasein sucrose consumption in all countries by ± 2% every year in the last decade. This increaseis greater than the increase in the world's population each year which is equal to ± 1.4% -1.6%. Based on a preliminary study of 12 students, an average salivary pH of 6.1 showedthat the pH of the saliva was acidic. Chewing gum can reduce the occurrence of caries in theteeth due to saliva which helps in reducing the number of bacteria in the oral cavity which isthe main cause of caries.This study aims to determine the differences in the pH of saliva chewing xylitol gumand sucrose in SDN 2 Guntung Paikat Banjarbaru. This research is a quasi-experimentaltype of research with One Group Pretest Post Test research design. The sampling techniquewas purposive sampling with a total sample of 66 students with data analysis using theIndependent Sample T-test.The results of this study showed the average pH of saliva before chewing xylitol gumwas 6,967, before chewing sucrose gum (big babol) was 7,073, while the average valueafter chewing xylitol gum was 7,270, after chewing sucrose gum was 6,624 with thedifference in value of xylitol gum was 0,303, and sucrose gum (big babol) was -0,448. Theunpaired t test results obtained p value = 0,000 (p = <0.05).In conclusion there is a difference in the pH of saliva chewing xylitol gum and sucrosein SDN 2 Guntung Paikat Banjarbaru. It is recommended that the public know thecomposition of the gum consumed and prefer sugar-free gum for the sake of oral health.